A Bibliometric Analysis of Islamic Work Ethics: Research Trends and Future Directions - Zaroni, Akhmad Nur; Lestari, Dirga (Al-Tijary, 2025)
Islamic Work Ethics (IWE) has been the focus of growing research, including its influence on organizational performance, leadership, and the development of work culture based on Islamic values. This study maps the trends, main themes, and research contributions on Islamic Work Ethics (IWE) globally through bibliometric analysis of scientific publications in 2012–2024 using Publish or Perish and VOSviewer. The results show three main phases of IWE development: (1) conceptual exploration in the Islamic finance and education sector (2012–2017), (2) application in Islamic value-based organizational management (2018–2019), and (3) its impact on performance, job satisfaction, and organizational justice (2019–2024). Malaysia, Indonesia, and Pakistan are the largest contributors, focusing on education, MSMEs, and Islamic banking. The study also uncovered research gaps, such as the global application of IWE, cross-cultural relations, and its influence on multicultural generations. This research offers strategic directions for the development of IWE in the Islamic education sector and modern organizations.